EVALUASI STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DI RUMAH SAKIT KHUSUS BEDAH HASTA HUSADA UNTUK MENINGKATKAN KOMPETENSI DAN KINERJA PEGAWAI - Hanafiah, Ali; Adiba, Farah; Hariyono, Angella Sevyandini; Ali Assegaf, Nurhayati (JOURNAL AKSES STIA MALANG, 2025)
The increasingly competitive business environment drives organizations to have superior and adaptive human resources (HR), especially in facing Society 5.0, which demands the utilization of advanced technology. This study aims to evaluate the HR development strategies at Hasta Husada Special Surgery Hospital. Using a qualitative approach through observation, interviews, and documentation, the study employs a descriptive analysis method.The findings reveal that the hospital's HR development program includes formal training, performance evaluation, direct training, job rotation, job transfer, temporary assignments, and interpersonal communication. However, several challenges were identified, such as unstructured training schedules, high transportation costs for training in remote locations, unequal access to training, and the absence of effective evaluation tools for assessing the program.Recommendations include setting clear objectives for HR development, recognizing staff as human capital, developing tools to measure program success, and adding evaluators to support optimal program implementation.